ANALYSIS OF THE PERFORMANCE OF PERSONAL TRAINNERS IN RELATION THE LAPSING OF DIRECTED PROGRAMS OF TRAINING TO THE PROMOTION OF THE HEALTH OF ITS CUSTOMERS (Fiep Bulletin - online, 2015)
The objective of this research was to verify as the personal trainers who act in Iguaçu Falls/PR are prescribing his programs of training and to inquire if these programs they are being projected in correct way so that he promotes the health of his clients. Participated of sample 22 personal trainners of 7 academies of the city of the Foz do Iguaçu/PR.  For it collects of facts, was utilized a questionnaire contendaining 10 objective questions and an open question.  After the collection of facts, was verifou that 59.1% of the interviewed ones do not carry through physical evaluation;  45,4% do not make anamnese;  86,4% do not apply PAR-Q;  that 31.8% consider osteoporose a primary risk for atherosclerosis, while only 13.6% consider the sedentarismo and the hipercolestherolemy as primary factors of risk.  The results had still pointed that 40.9% of the interviewed ones do not carry through no form of nutricional orientation;  that only 4.6% of the interviewed ones are experts of the benefits of the physical exercise for hiperthensos and 68,2 %  do not know which the normal levels of glicemia of an apparently healthy adult.  When if it dealt with the methods of training for beginning, only 22.7% costumam to use the method Alternated for Segment, that is indicated.  With base in these results it can be concluded that great part of the personal trainners does not possess theoretical and scientific basement and inexists on the part of many the basic qualification to elaborate, to prescribe and to guide programs of physical exercises that promote with cientific and security the health and the welfare of its customers.
Keywords: .